Estrat??gias transmidi??ticas : as opera????es de intera????o entre estudantes e institui????es de ensino superior mediadas por m??dias digitais - Garcia, Jana??na Leonardo (2012)
This study proposes a research and critical reflection about social networks implications, while new space communication carrier updates the dynamic mediation of symbolic exchanges between subjects, generated in the young people attitude. The effort, inspired by the discursive semiotics and cultural studies, it begins with an analysis regarding the social networks capability to influence the construction of meaning that will apply in the choices for students in the third year of the Centro de Ensino Leonardo Da Vinci- Unidade Sul de Bras??lia, relative to which graduate education institutions (IES) to attend and what career to pursue, beyond to evaluate how is the interaction process with four IES of Distrito Federal. Moreover, we seek to find the construct process of meaning agents communication within social networks Facebook and Twitter . We realized after investigation, that the construction of meaning in this virtual environment, eventually contemplate some aspects of individual and collective reality. Young people test the new ambiences, but their practices still tend to obey the logic and analog traditional without effecting the sense movement and be influenced by the social networks themselves to the issues involving in decisions relevant to the individual.